Essays on India's political economy - Sarangi, Prakash (New Delhi K.W publishers, 2014)
Indian Political Economy is divided into three phases: (1) Nationalist Political Economy (1947-68); (2) Populist Political Economy (1969-1990) and (3) Competitive Political Economy (1991-). A running theme in these essays is that while political actors face uncertainty in a competitive political economy, the citizens, as consumers of public policies, are further empowered to question, accept or reject any policy initiative.
Keywords: Politics and government; Economic policy; India